(untitled) (Research, Society and Development, 2025)
This systematic review aimed to identify and synthesize data on the physical and physicochemical characteristics of stingless bee honey produced in Brazil. A total of 231 samples were analyzed across the selected studies, with most originating from the Northeast region. Key parameters evaluated included moisture, pH, acidity, sugars, and phenolic compounds. The findings reveal significant variability among samples and consistent deviations from standards established for Apis mellifera honey, particularly in moisture content, free acidity, HMF levels, and diastase activity. These differences highlight the need for specific regulatory standards for stingless bee honey in Brazil. The unique composition of this product underscores its distinct physicochemical profile and the importance of tailored quality criteria to ensure appropriate classification, safety, and market development.